Coordinated expansion of both memory T cells and NK cells in response to CMV infection in humans. Issue 5 (11th March 2016) - Bayard, Charles; Lepetitcorps, Hélène; Roux, Antoine; Larsen, Martin; Fastenackels, Solène; Salle, Virginie; Vieillard, Vincent; Marchant, Arnaud; Stern, Marc; Boddaert, Jacques; Bajolle, Fanny; Appay, Victor; et al.
Abstract : Latent HCMV infection (without replication) is sufficient for NKG2C+ CD57+ NK cells to persist in healthy individuals but is not necessarily required in old age. HCMV infection is shaping both innate and adaptive immunity by driving inflation of differentiated T and NK cells. Abstract : NK cells are key players in the fight against persistent viruses. Human cytomegalovirus (HCMV) infection is associated with the presence of a population of CD16 + CD56 dim NKG2C + NK cells in both acutely and latently infected individuals. Here, we studied the nature of these terminally differentiated NK cells in different human populations infected with HCMV: healthy donors stratified by age, thymectomized individuals, pregnant women suffering from primary CMV infection, and lung transplant patients. Both CD16 + CD56 dim NK‐ and CD8 T‐cell phenotypes as well as functional capacities were determined and stratified according to age and/or CMV event. Similarly to T‐cell responsiveness, we observe an accumulation over time of NKG2C + NK cells, which preferentially expressed CD57. This accumulation is particularly prominent in elderly and amplified further by CMV infection. Latent HCMV infection (without replication) is sufficient for NKG2C + CD57 + NK cells to persist in healthy individuals but is not necessarily required in old age. Collectively, the present work supports the emerging concept that CMV shapes both innate and adaptive immunity in humans.